Bihar Second Five-Year Plan Progress Report for the Period Ending March, 1961 - Planning Commission (Planning Commission, 1961)
Agricultural Production, Minor Irrigation, Soil Conservation, Land Development, Marketing, Animal Husbandry, Dairying and Milk Supply, Forest, Fisheries, C.P. and N.E.S., Co-operation, Gram Panchayat, Major and Medium Irrigation Projects, Power Projects, Industry, Roads, Road Transport, Education, Health, Housing, Labour Welfare, Welfare of Scheduled Tribes, Scheduled Castes and Backward Classes, Social Welfare, Publicity and Propaganda, Statistics.
Bihar